Corporate Financial Policy and Taxation in a Growing Economy - Feldstein, Martin; Green, Jerry; Sheshinski, Eytan (Quarterly Journal of Economics, 1979)
I. A model of financial equilibrium, 412.—IL Effects of changes in the profit tax rate, 418.—III. Effects of changes in the taxation of retained earnings, 423.—IV. The nonneutrality of the corporate income tax, 427.—V. Conclusion, 430.